2020
DOI: 10.1029/2019jg005451
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric Differences in Trophic Status of Scleractinian Corals From Weizhou Island, Northern South China Sea: Implication for Their Different Environmental Stress Tolerance

Abstract: The knowledges of trophic status (i.e., autotrophy/heterotrophy) of corals are helpful for understanding the mechanisms driving their environmental stress tolerance and bleaching resilience. We conducted this study to elucidate the differences in trophic status among corals of different genera and then explore the implication of trophic status for their different environmental stress tolerance. In this study, 117 coral samples including five genera (i.e., relatively stress-tolerant massive genera Porites, Favi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…13 C z values, and vice versa (Porter et al, 1989;Swart et al, 2005a;Wooldridge, 2013;Linsley et al, 2019;Xu et al, 2020). Our results show that δ 13 C z was significantly positively related to ZD (Figure 4).…”
Section: Spatial Variations and Controlling Factors Of The Autotrophic Ability Of Coral In The Scssupporting
confidence: 49%
See 1 more Smart Citation
“…13 C z values, and vice versa (Porter et al, 1989;Swart et al, 2005a;Wooldridge, 2013;Linsley et al, 2019;Xu et al, 2020). Our results show that δ 13 C z was significantly positively related to ZD (Figure 4).…”
Section: Spatial Variations and Controlling Factors Of The Autotrophic Ability Of Coral In The Scssupporting
confidence: 49%
“…In our study, there were no significant differences in SSS and pH values among the three CRRs. Alamaru et al, 2009;Xu et al, 2020). We analyzed the correlation between ZD and δ 13 C z of each coral sample from the three coral reefs, and the results showed that ZD and δ 13 C z were positively correlated, as shown in Figure 4.…”
Section: Environmental and Water Parametersmentioning
confidence: 98%
“…The matter source of sediment from land or ocean and fluctuation of relative sea level on the coast of Weizhou Island have not been well estimated. Some research has been carried out to assess the fluctuation of relative sea level on Weizhou Island [25], and a number of studies have investigated the trophic status of corals and permeable sandy sediment using carbon as an indicator [26,27]. However, a detailed understanding of the matter sources of coastal sediment and their environmental implications for relative sea level fluctuations on Weizhou Island is still largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, natural abundance stable carbon (δ 13 C) and nitrogen (δ 15 N) isotopes of the coral host and algal endosymbionts can be used to broadly estimate the proportionate contribution of photoautotrophy and heterotrophy to coral tissues under natural and experimental conditions (e.g., Muscatine et al 1989; Rodrigues and Grottoli 2006; Ferrier‐Pagès et al 2011). Trophic strategies of corals have also been identified using tissue stable isotopes in corals from Hong Kong (Conti‐Jerpe et al 2020), the South China Sea (Xu et al 2020), and Maldives (Radice et al 2019), and shown to vary along a natural gradient of primary productivity among the Southern Line Islands in the Central Pacific (Fox et al 2018). However, unlike some other ecological disciplines, isotope mixing model approaches have not been widely adapted in coral research to evaluate the proportionate contribution of nutritional sources to coral diets.…”
mentioning
confidence: 99%